From the Regional Symposium to Our Own Journal Publication:Forthe SoundDevelopmem of ChemicalEngineering in ASEAN - Hiroo Niiyama (ASEAN Journal of Chemical Engineering, 2001)
Regional symposium on Chemical Engil.1eeringwas first held in 1994 in Manila, Philippines. Since then, the symposium has developed quite significantly in terms of publishing papers in the said field. However, any development stagnates if scholars do not make effortsto further improve the present system. This paper analyzes such underlying problems in the academic community of different regions. Based on these problems, the ad hoc preparatory committee hence sees the need to propose the foundation of a Chemical Engineering Journal.